2004
DOI: 10.2527/2004.8261847x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a twin strain of Saccharomyces cerevisiae live cells on mixed ruminal microorganism fermentation in vitro1

Abstract: This experiment was designed to investigate the effects of different concentrations (0, 0.33, 0.66, 0.99, and 1.32 g/L) of a twin-strain of Saccharomyces cerevisiae live cells on in vitro mixed ruminal microorganism fermentation of corn starch, soluble potato starch, and sudangrass hay (60.5%, DM basis) plus concentrate mixture (39.5%, DM basis). Ruminal fluid was collected from two dairy cows, mixed with phosphate buffer (1:2), and incubated (30 mL) anaerobically at 38 degrees C for 6 and 24 h with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
78
1
14

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 29 publications
23
78
1
14
Order By: Relevance
“…In the present study, the rumen ammonia concentration was not affected by the yeast addition, as reported by others (Lila et al, 2004;Mwenya et al, 2005), although slight decreases in the ammonia concentration by LYC and YC for the L-NDF diet were observed. Decreased ammonia concentrations in the rumen caused by Saccharomyces cerevisiae were reported by Abd-El-Ghani (2004) and may indicate lower protein decomposition as well as faster flow of undegraded protein to the duodenum.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, the rumen ammonia concentration was not affected by the yeast addition, as reported by others (Lila et al, 2004;Mwenya et al, 2005), although slight decreases in the ammonia concentration by LYC and YC for the L-NDF diet were observed. Decreased ammonia concentrations in the rumen caused by Saccharomyces cerevisiae were reported by Abd-El-Ghani (2004) and may indicate lower protein decomposition as well as faster flow of undegraded protein to the duodenum.…”
Section: Resultssupporting
confidence: 88%
“…This effect was not observed in the present study. Lila et al (2004) found in their in vitro study that yeast increased total VFAs and elevated levels of propionate during batch culture incubations, which was confirmed in the case of the LYC additive for the L-NDF diet. Nonetheless, in the experiments conducted by Newbold et al (1995), LYC did not affect VFA concentrations.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Similarly, Lila et al (2004) observed no effect of a twin-strain of Saccharomyces cerevisiae live cells (0.33 to 1.32 g/l) on pH. In contrast, Bach et al (2007) demonstrated that yeast supplementation (Saccharomyces cerevisiae Strain CNCM I-1077) to dairy cattle (5 g/day) contributes to the rumen environment by enhancing the ruminal pH.…”
Section: Discussionmentioning
confidence: 96%
“…After sampling, the bottle was immediately and anaerobically warmed in a portable incubator (39 ± 1°C). Ruminal fluid was transferred to the laboratory and then filtered through four layers of surgical gauze into a polypropylene beaker under flushing with O 2 -free CO 2 CO 3 , and 600 mg cysteine hydrochloride) in accordance with the method of Lila et al [14]. The ruminal fluid (10 ml) and buffer (20 ml) were immediately mixed in a 50 ml polypropylene test tube containing a substrate of micronised wood powder.…”
Section: In Vitro Experimentsmentioning
confidence: 99%